2022
DOI: 10.1039/d2ob00386d
|View full text |Cite
|
Sign up to set email alerts
|

Recent synthetic methodologies for imidazo[1,5-a]pyridines and related heterocycles

Abstract: Imidazo[1,5-a]pyridine is a significant structural component of a huge number of agrochemicals and pharmaceuticals. The synthesis of imidazo[1,5-a]pyridine has been a subject of intense research for numerous decades. A large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…[36][37][38][39][40] A number of methods have been reported for the synthesis of imidazo [1,5-a]pyridine derivatives via heterocyclization. 41,42 The strategy based on condensation of pyridine-2-carboxaldehydes with amines followed by decarboxylative C(sp 3 )-H amination has gained a widespread recognition in recent years. A variety of chemical oxidative systems were applied for imidazo [1,5-a]pyridine core construction from pyridine-2-carboxaldehydes and amines: Cu(II)/air, 43 Cu(I)/ air, 44 Cu(II)/I 2 /DTBP, 45 Cu-based MOF/air, 46,47 iodine, [48][49][50] I 2 / TBHP, 51 and MnO 2 52 (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40] A number of methods have been reported for the synthesis of imidazo [1,5-a]pyridine derivatives via heterocyclization. 41,42 The strategy based on condensation of pyridine-2-carboxaldehydes with amines followed by decarboxylative C(sp 3 )-H amination has gained a widespread recognition in recent years. A variety of chemical oxidative systems were applied for imidazo [1,5-a]pyridine core construction from pyridine-2-carboxaldehydes and amines: Cu(II)/air, 43 Cu(I)/ air, 44 Cu(II)/I 2 /DTBP, 45 Cu-based MOF/air, 46,47 iodine, [48][49][50] I 2 / TBHP, 51 and MnO 2 52 (Scheme 2a).…”
Section: Introductionmentioning
confidence: 99%
“…The promising properties and applications of these molecules have always inspired organic chemists to establish some attractive synthetic routes for achieving those high-valued N -heterocyclic frameworks in the last few decades. However, a careful literature survey found that most conventional methods to achieve imidazo­[1,5- a ]­pyridines had limitations for the synthesis of 3-acyl imidazo­[1,5- a ]­pyridines . Furthermore, synthetic routes to 3-acyl imidazo­[1,5- a ]­pyridines, traditionally, include two methods, in which all the desired products achieved successfully by both strategies were afforded through multistep reactions employing 2-pyridinemethanamines as substrates under suitable conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Both imidazo [1,5-a]pyridine and benzimidazole, which consist of an imidazole moiety fused to a hexacyclic aromatic ring, are important biologically active nitrogencontaining heterocycles. They are well-known for their medicinal use and material applications [1,2]. Imidazo [1,5-a]pyridine and benzimidazole derivatives possess various bioactivities, including antimicrobial, anthelmintic, antiviral, anticancer, and antihypertensive activities.…”
Section: Introductionmentioning
confidence: 99%